Update on Calcium Signaling in Cystic Fibrosis Lung Disease - Rimessi, Alessandro; Vitto, Veronica A. M.; Patergnani, Simone; Pinton, Paolo (Frontiers in Pharmacology, 2021)
Cystic fibrosis (CF) is an autosomal recessive disorder characterized by mutations in the cystic fibrosis transmembrane conductance regulator gene, which causes multifunctional defects that preferentially affect the airways. Abnormal viscosity of mucus secretions, persistent pathogen infections, hyper inflammation, and lung tissue damages compose the classical pathological manifestation refereed to CF lung disease. Among the multifunctional defects associated with defective CFTR, increasing evidence supports the relevant role of perturbed Calcium (Ca2+) signaling in the pathophysiology of CF lung disease. The Ca2+ ion is a critical player in cell functioning and survival. Its intracellular homeostasis is maintained by a fine balance between channels, transporters, and exchangers, mediating the influx and efflux of the ion across the plasma membrane and the intracellular organelles. An abnormal Ca2+ profile has been observed in CF cells, including airway epithelial and immune cells, with heavy repercussions on cell function, viability, and susceptibility to pathogens, contributing to pro-inflammatory overstimulation, organelle dysfunction, oxidative stress, and excessive cytokines release in CF lung. This review discusses the role of Ca2+ signaling in CF and how its dysregulation in airway epithelial and immune cells contributes to hyperinflammation in the CF lung. Finally, we provide an outlook on the therapeutic options that target the Ca2+ signaling to treat the CF lung disease.